Failure Mode and Effect Analysis (FMEA) and Root Cause Analysis (RCA) for Urea Fertilizer Production Risk Mitigation - A'yun, Aisya Qurratul; Iriani (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
The production of urea fertilizer is one of the most important processes in the agricultural industry, but it cannot be separated from various risks that can interfere with its smooth operation. This research aims to identify and mitigate the risks involved in urea fertilizer production using the Failure Mode and Effect Analysis (FMEA) and Root Cause Analysis (RCA) methods. The results show that some of the major risks in urea fertilizer production include equipment failure, raw material supply disruption, and operational errors. By applying FMEA and RCA, the company can identify the root causes of the problems and develop effective mitigation strategies. The implementation of these mitigation actions is expected to improve production efficiency and reduce downtime, thus ensuring better production continuity.